2014
DOI: 10.1155/2014/786480
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenGiardia duodenalisand Coinfection with Other Diarrhea-Causing Pathogens in India

Abstract: Giardia duodenalis, is often seen as an opportunistic pathogen and one of the major food and waterborne parasites. Some insights of Giardia infestation in a diarrhoea-prone population were investigated in the present study. Our primary goal was to understand the interaction of this parasite with other pathogens during infection and to determine some important factors regulating the diarrhoeal disease spectrum of a population. Giardia showed a steady rate of occurrence throughout the entire study period with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Co-infection by multiple groups of enteric pathogens has been demonstrated to be the norm in diarrhoea cases [20]. The possible reasons are: (i) that when one intestinal pathogen infects the body, the infection rate of other pathogens increases [21]; (ii), these are foodborne pathogens and can be found in the same contaminated foods increasing the likelihood of mixed infections in risk populations. It has been reported that co-infections with multiple enteric pathogens occur mainly in zones with poor quality of food, drinking water and poor sanitary conditions in the environment [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Co-infection by multiple groups of enteric pathogens has been demonstrated to be the norm in diarrhoea cases [20]. The possible reasons are: (i) that when one intestinal pathogen infects the body, the infection rate of other pathogens increases [21]; (ii), these are foodborne pathogens and can be found in the same contaminated foods increasing the likelihood of mixed infections in risk populations. It has been reported that co-infections with multiple enteric pathogens occur mainly in zones with poor quality of food, drinking water and poor sanitary conditions in the environment [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Giardia transmission is not as well understood as Cryptosporidium, mostly because typing approaches have been suboptimal and routine surveillance in developed countries has focussed on the link to travel, rather than indigenous sources of infection [143]. Hygiene linked to water is important and occurrence in developing countries shows no relationship to rainfall [144]. However, the infection is common, and determining any change due to climate may be difficult.…”
Section: Protozoamentioning
confidence: 99%
“…Generally, this is due to the diagnostic laboratories not continuing to search for subsequent pathogens once they have diagnosed the first. This represents a possible gap in knowledge, as previous studies from developing countries have demonstrated that the presence of other pathogens such as Heliobacter pylori, Vibrio cholerae and rotavirus have been associated with Giardia co-infection [42][43][44]. Research on the prevalence of coinfections in returned travellers and whether identifying these co-infections is practical may be warranted in the future.…”
Section: Discussionmentioning
confidence: 99%